(untitled) (Orthodontic Journal of Nepal, 2025)
Anterior open bite is a challenging malocclusion with multifactorial etiology involving skeletal, dentoalveolar, and functional components such as tongue thrusting. Management in adults is difficult due to the absence of growth potential and concerns regarding long-term stability. This case report describes non-surgical management of a 22-year-old male with a 4 mm anterior open bite, tongue thrusting habit, proclined incisors, and increased lower facial height on a skeletal Class I base using a modifid MEAW (Multiloop Edgewise Archwire) technique. The case is unique due to integration of simplified MEAW mechanics using accentuated/reverse curve NiTi archwires, anterior box elastics, and simultaneous habit interception. Active treatment was completed in 16 months with adjunctive myofunctional therapy, achieving positive overbite, ideal overjet, Class I occlusion, elimination of tongue thrusting, and improved facial esthetics. This case highlights that modified MEAW with anterior box elastics and habit control is an effective, practical, nonsurgical approach for managing dentoalveolar anterior open bite in adults.